2022
DOI: 10.3390/polym14142885
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strength of Triply Periodic Minimal Surface Lattices Subjected to Three-Point Bending

Abstract: Sandwich panel structures (SPSs) with lattice cores can considerably lower material consumption while simultaneously maintaining adequate mechanical properties. Compared with extruded lattice types, triply periodic minimal surface (TPMS) lattices have light weight but better controllable mechanical properties. In this study, the different types of TPMS lattices inside an SPS were analysed comprehensively. Each SPS comprised two face sheets and a core filled with 20×5×1 TPMS lattices. The types of TPMS lattices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…There exists an inverse relationship between the mechanical properties of G-structure and unit size. Among specimens with the same unit size, those with a relative density of 30% demonstrated higher mechanical strength and elastic modulus (Lin et al 2022;Pires et al 2021). However, although porous specimens with a relative density of 20% do not possess comparable mechanical strength to their counterparts, it exhibited lower elastic modulus and larger porosity, which were advantageous for promoting bone tissue nutrient transfer and enhancing bone ingrowth ability (Lv et al 2022b;Wang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists an inverse relationship between the mechanical properties of G-structure and unit size. Among specimens with the same unit size, those with a relative density of 30% demonstrated higher mechanical strength and elastic modulus (Lin et al 2022;Pires et al 2021). However, although porous specimens with a relative density of 20% do not possess comparable mechanical strength to their counterparts, it exhibited lower elastic modulus and larger porosity, which were advantageous for promoting bone tissue nutrient transfer and enhancing bone ingrowth ability (Lv et al 2022b;Wang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, triply periodic minimal surfaces (TPMS) have garnered significant attention from researchers in the field of 3D printing porous structures due to their unique properties. TPMS surfaces exhibit smoothness and interconnected pore heights, allowing for precise control over the overall structure through implicit functions (Li et al 2022). Consequently, It present an exceptional solution for designing and modeling porous structures in 3D printed bone grafts (Günther et al 2022;Lv et al 2022a;Shen et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Trigonometrically, the gyroid surface can be approximated by the equation: sin(x)cos(y) + sin(y)cos(z) + sin(z)cos(x) = 0. It was demonstrated that with sandwich panel structures with minimal surfaces, particularly gyroid, cores considerably lower material consumption while simultaneously maintaining mechanical properties [22]. Gyroids make MEX parts stronger and lighter.…”
Section: Minimal Surfacesmentioning
confidence: 99%
“…roid surface can be approximated by the equation: sin(x)cos(y) + sin = 0. It was demonstrated that with sandwich panel structures with ticularly gyroid, cores considerably lower material consumption maintaining mechanical properties [22]. Gyroids make MEX parts Due to the complexity of this structure, it was designed by computational means, but was not able to be manufactured until the arrival of additive manufacturing.…”
Section: Minimal Surfacesmentioning
confidence: 99%
“…Lattice structures have been studied in the context of four different material classes: resins, thermoplastics, ceramics and metals. Research on thermoplastics, 8 resins 9,10 and ceramics 11 focuses on the bending and compression behaviour of a range of lattice geometries. On the metal printing side, Ti-6Al-4V electron beam melting (EBM) 12 and 316L Stainless Steel Powder Bed Fusion (PBF) 13 printed lattices were investigated and modelled.…”
Section: Introductionmentioning
confidence: 99%